2013
DOI: 10.1111/cei.12066
|View full text |Cite
|
Sign up to set email alerts
|

Increased Dickkopf-1 expression in patients with unexplained recurrent spontaneous miscarriage

Abstract: SummaryWnt pathways play an important role in pre-implantation embryo development, blastocyst implantation, and post-implantation uterine decidualisation. However, little is known about the potential role that Wnt signaling plays in patients with unexplained recurrent spontaneous miscarriage (URSM), and no single biomarker with a high predictive value of maternally caused URSM has been identified. We aim to study the molecular mechanisms by which the Wnt pathway controls the progression of early pregnancy by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 31 publications
(37 reference statements)
1
25
0
Order By: Relevance
“…Therefore, downregulation of the pathway could contribute to failed placentation and shallow trophoblast invasion observed in these pregnancies. Along those lines, elevated levels of Dkk1 were detected in women with recurrent abortions (Bao et al, 2013). Interestingly, cytomegalovirus (CMV) infection, a putative cause of spontaneous abortion and preterm delivery, was shown to decrease trophoblast proliferation and invasion involving inhibition of Wnt signaling.…”
Section: Wnt Signaling In Placenta and Trophoblastmentioning
confidence: 90%
“…Therefore, downregulation of the pathway could contribute to failed placentation and shallow trophoblast invasion observed in these pregnancies. Along those lines, elevated levels of Dkk1 were detected in women with recurrent abortions (Bao et al, 2013). Interestingly, cytomegalovirus (CMV) infection, a putative cause of spontaneous abortion and preterm delivery, was shown to decrease trophoblast proliferation and invasion involving inhibition of Wnt signaling.…”
Section: Wnt Signaling In Placenta and Trophoblastmentioning
confidence: 90%
“…Additionally, the Wingless (Wnt) signaling pathway plays an important role in the differentiation and migration of trophoblasts (35). Abnormal expression of Wnt signaling has been reported to occur in placental tissue from clinical cases of spontaneous abortion (36) and preeclampsia (37), suggesting that aberrant Wnt signaling contributes to the pathogenesis of these diseases of pregnancy. Wnt ligands are evolutionarily conserved and couple to various receptors to activate different downstream pathways.…”
mentioning
confidence: 99%
“…Accumulating data indicated that abnormal expression of Wnt/β‐catenin signaling might be associated with pathogenesis of URSA (Bao et al, ; Li et al, ). In the present study, we found that besides the decreased expression of active β‐catenin, WNT2 was also significantly reduced in villi of URSA compared to that of healthy women.…”
Section: Discussionmentioning
confidence: 99%